Clinical and molecular characterization of Indian patients with fructose‐1, 6‐bisphosphatase deficiency: Identification of a frequent variant (E281K). (18th May 2018) - Bhai, Pratibha; Bijarnia‐Mahay, Sunita; Puri, Ratna D.; Saxena, Renu; Gupta, Deepti; Kotecha, Udhaya; Sachdev, Anil; Gupta, Dhiren; Vyas, Vyomesh; Agarwal, Divya; Jain, Vivek; Bansal, Rajeev K.; et al.
Abstract: Fructose‐1, 6‐bisphosphatase deficiency is an autosomal recessive disorder of gluconeogenesis caused by genetic defect in the FBP1 gene. It is characterized by episodic, often life‐threatening metabolic acidosis, liver dysfunction, and hyperlactatemia. Without a high index of suspicion, it may remain undiagnosed with devastating consequences. Accurate diagnosis can be achieved either by enzyme assay or gene studies. Enzyme assay requires a liver biopsy and is tedious, invasive, expensive, and not easily available. Therefore, genetic testing is the most appropriate method to confirm the diagnosis. Molecular studies were performed on 18 suspected cases presenting with episodic symptoms. Seven different pathogenic variants were identified. Two common variants were noted in two subpopulations from the Indian subcontinent; p.Glu281Lys (E281K) occurred most frequently (in 10 patients) followed by p.Arg158Trp (R158W, in 4 patients). Molecular analysis confirmed the diagnosis and helped in managing these patients by providing appropriate genetic counseling. In conclusion, genetic studies identified two common variants in the Indian subcontinent, thus simplifying the diagnostic algorithm in this treatable disorder.